2019
DOI: 10.1002/ecs2.2563
|View full text |Cite
|
Sign up to set email alerts
|

Life in a northern town: rural villages in the boreal forest are islands of habitat for an endangered bat

Abstract: Citation: Thomas, J. P., and T. S. Jung. 2019. Life in a northern town: rural villages in the boreal forest are islands of habitat for an endangered bat.Abstract. Urban development is detrimental to many wildlife species; however, endangered little brown bats (Myotis lucifugus) may be attracted to human settlements, making them a synurbic species. Buildings likely provide high-quality roosting habitat, which may be a limiting factor in the boreal forest where trees are typically small and potentially unsuitabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 80 publications
(209 reference statements)
0
14
1
Order By: Relevance
“…The absence of data on natural roosts is a limitation; however, we expect that roosting trees are scarce in our study area, given the prevalence of young forest and regenerating burn, where suitable large‐diameter trees and snags may be scarce (Crampton and Barclay 1998, Jung 2020). Interestingly, bat activity levels in this study were substantially lower than in rural villages with much smaller human populations and urban footprints (Thomas and Jung 2019). This may be attributed to the broad distribution of potential roosts in the Whitehorse area; conversely, anthropogenic roosts are confined to a comparatively small area within rural villages, perhaps resulting in higher concentrations of bat activity.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…The absence of data on natural roosts is a limitation; however, we expect that roosting trees are scarce in our study area, given the prevalence of young forest and regenerating burn, where suitable large‐diameter trees and snags may be scarce (Crampton and Barclay 1998, Jung 2020). Interestingly, bat activity levels in this study were substantially lower than in rural villages with much smaller human populations and urban footprints (Thomas and Jung 2019). This may be attributed to the broad distribution of potential roosts in the Whitehorse area; conversely, anthropogenic roosts are confined to a comparatively small area within rural villages, perhaps resulting in higher concentrations of bat activity.…”
Section: Discussioncontrasting
confidence: 54%
“…Several acoustic studies in southern Yukon reported that little brown bats were the most common bat species by far, albeit at low densities (Slough and Jung 2008, Thomas et al 2019, Thomas and Jung 2019, Jung 2020). Other bat species are likely present but rarely detected (Jung et al 2006, Slough et al 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ecological conditions in 20% of YRDUA deteriorated, and the ecological conditions in 40% increased from 1995 to 2010 [19]. The improvement in habitat quality in urban areas has also been testified in accelerating vegetation growth [21,22,58] and enhancing species richness [18,20] in urban environments compared to those in rural equivalents.…”
Section: Nonlinear Relationship Between Habitat Quality and Urbanizatmentioning
confidence: 99%
“…However, the correlation trends are not completely consistent among different studies. The relationships between urbanization and the diversity of plants [16], amphibians [17] and mammals [18] have been separately analyzed, and it was found that there were no negative and even positive effects in urban-rural gradients. In addition, using non-field survey approaches, the positive influence of urbanization on environmental variation has been observed at the city, regional and national scales.…”
Section: Introductionmentioning
confidence: 99%